A composite electrolyte for low-stress lithium battery copper foil and a method for preparing low-stress lithium battery copper foil
Patent Information
- Application Number
- CN202611323602.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
现有电解沉积工艺会配套烘箱烘烤、退火炉退火等后处理工序以释放铜箔原生残余应力,但常规后处理方案均未对干燥、退火条件及冷却速率进行精准管控,这也导致了处理过程中极易生成新的二次热应力
1、本发明构建了光亮剂-整平剂-抑制剂-应力消除剂的低应力铜箔专用复合电解液体系,其中,光亮剂可细化铜箔晶粒,提升表面光亮性,同时抑制晶粒异常生长,减少晶界缺陷;整平剂可吸附在阴极表面,使铜离子沉积均匀,降低表面粗糙度,避免局部沉积凸起导致的应力集中;抑制剂能够抑制铜箔表面局部过度沉积,调控铜离子沉积速率,保证晶粒致密生长;应力消除剂为核心添加剂,作用为通过吸附在阴极表面调整铜离子沉积方式,减少晶界缺陷和晶格畸变,从而破坏应力累积;本发明通过精准控制各添加剂的种类和用量,从铜离子沉积源头降低铜箔内应力。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to a composite electrolyte for low-stress lithium-ion battery copper foil and a method for preparing low-stress lithium-ion battery copper foil, belonging to the field of lithium-ion battery copper foil preparation technology. Background Technology
[0002] As the core current collector of lithium-ion batteries' negative electrode, copper foil plays a crucial role in electron transport and active material support. Its mechanical properties, internal stress level, surface quality, and dimensional stability directly determine the capacity, cycle life, processing yield, and safety of lithium-ion batteries. With the lithium battery industry moving towards higher energy density, higher rate, and longer cycle life, market demand for 6 μm ultrathin lithium-ion battery copper foil continues to rise, while the comprehensive performance requirements for low internal stress, high tensile strength, high elongation, and low warpage are becoming increasingly stringent. High-stress copper foil is prone to warping, breakage, and poor slitting during production, resulting in low yield. Downstream electrode processing is susceptible to defects such as uneven coating, rolling cracking, and die-cutting burrs, reducing processing yield. During battery cycling, the copper foil can also deform and crack due to the expansion and contraction of the active material, damaging the electrode structure, shortening the cell's cycle life, and posing safety risks.
[0003] Electrolytic deposition is widely used in the preparation of lithium-ion battery copper foil due to its high production efficiency and low cost. The traditional electrolytic deposition process mainly involves copper dissolution and solution preparation, foil electrolysis, and post-processing. Influenced by factors such as the surface morphology of the cathode roller, impurities, and process parameters, copper ions are prone to misalignment and slippage during electrolytic deposition, disrupting the symmetry of the entire crystal and generating internal stress. By introducing suitable additives into the electrolyte, the grain size of the electrolytic copper foil can be refined, and the growth of crystal planes such as (111) and (220) can be moderately controlled, significantly alleviating residual stress and copper foil warping problems. Therefore, electrolyte formulation optimization is the core technical path for preparing low-stress copper foil.
[0004] The inventors discovered that N-(3-sulfopropyl)-saccharin sodium and functional additives such as JC-U2 and JC-IBE can reduce grain boundary defects and lattice distortion, release the original tensile stress of electrodeposition, and effectively reduce copper foil warpage. However, composite electrolyte systems adapted to the preparation of low internal stress copper foil based on the above functional additives are still relatively rare. As shown in Chinese patents CN201510148125.3, CN201910247097.9, CN202410403327.7, and CN201210492733.2, existing electrolyte systems for preparing low-stress copper foil often use gelatin and collagen-based components as effective stress-reducing agents. These substances rely on adsorption on the cathode surface to hinder the reduction of copper ions and achieve grain refinement. However, this approach has many drawbacks: excessive adsorption of collagen-based components can exacerbate the oxidation and corrosion of the anode plate, shorten the anode replacement cycle, increase production costs, and reduce production efficiency. At the same time, excessive collagen can increase the brittleness of the copper foil, making it more prone to tearing defects during production. In addition, collagen is prone to spoilage and deterioration during storage, which can clog additive delivery pipelines and cause fluctuations in the mechanical properties of the copper foil. Furthermore, although a few technical solutions (such as Chinese patents with application numbers CN202411735992.2 and CN202411026315.3) use N-(3-sulfopropyl)-saccharin sodium as a stress-relieving component in order to simultaneously balance the core properties of copper foil such as internal stress, tensile strength, and elongation, these solutions still retain the use of collagen, and the additive system is adapted to a chlorine-containing electrolyte. Within the range of chloride ion addition in the above solutions, chloride ions have strong crystal plane selective adsorption characteristics, which can preferentially adsorb onto the (111) crystal plane of copper and reduce its surface energy, inducing the preferential growth of grains along the (111) direction; the difference in grain orientation between columnar crystals leads to the generation of internal stress. At the same time, chloride ions also accelerate the reduction rate of copper ions at local protrusions of copper foil, induce dendrites and burrs and other morphological defects, and form stress concentration at the dendrite roots. Under the combined influence of the internal stress caused by the orientation differences between the columnar crystals and the stress concentration effect at the dendrite roots, the internal stress of copper foil is prone to exhibit significant spatial unevenness. While a single sodium saccharin-based stress reliever can only improve the micro-stress caused by microscopic lattice distortion, it is difficult to fundamentally eliminate the macroscopic stress unevenness caused by abnormal grain orientation and morphological defects. Therefore, the internal stress control effect of the above-mentioned schemes remains relatively limited.
[0005] Besides the electrolyte formulation, the electrolysis and post-processing conditions of raw foil also have a significant impact on the internal stress of lithium-ion battery copper foil. Existing electrolytic deposition processes are accompanied by post-processing steps such as oven baking and annealing furnace annealing to release the original residual stress of the copper foil. However, conventional post-processing schemes do not precisely control the drying, annealing conditions, and cooling rates, which makes it easy to generate new secondary thermal stresses during the processing.
[0006] In summary, functional additives such as N-(3-sulfopropyl)-saccharin sodium, JC-U2, and JC-IBE can effectively regulate the microstructure of electrodeposited copper layers and release residual internal stress, making them a class of highly efficient stress-relieving functional components. However, in existing technologies, low residual stress electrolyte systems with excellent comprehensive performance, constructed using the above-mentioned substances as the core, are still very scarce. Therefore, developing novel compound electrolyte systems based on the above-mentioned additives and matching them with suitable electrolytic preparation processes has significant engineering and technical value for achieving stable mass production of low-stress, high-mechanical-performance lithium-ion battery copper foil. Summary of the Invention
[0007] To address existing problems, this invention provides a composite electrolyte for low-stress lithium-ion battery copper foil and a method for preparing low-stress lithium-ion battery copper foil. The composite electrolyte uses N-(3-sulfopropyl)-saccharin sodium and stress-relieving agents such as JC-U2 and JC-IBE as core additives, combined with brighteners, leveling agents, and inhibitors. It relies on a multi-component synergistic mechanism to regulate electrodeposition crystallization behavior, thereby significantly reducing residual internal stress in the copper foil. Simultaneously, the low-stress lithium-ion battery copper foil preparation process based on this composite electrolyte can simultaneously achieve comprehensive mechanical properties of low residual stress, high tensile strength, and high elongation in the copper foil, meeting the industrial continuous mass production requirements for 6 μm ultrathin lithium-ion battery copper foil.
[0008] The technical solution of this invention is as follows: This invention provides a composite electrolyte for low-stress lithium-ion battery copper foil, comprising an electrolyte and additives. The electrolyte comprises copper sulfate and sulfuric acid, and the additives comprise: a brightener, a leveling agent, an inhibitor, and a stress reliever. The brightener is sodium thiazolinyl dithiopropane sulfonate; the leveling agent is hydroxyethyl cellulose; the inhibitor is polyethylene glycol; and the stress reliever is selected from one of N-(3-sulfopropyl)-saccharin sodium, JC-U2, or JC-IBE.
[0009] Furthermore, the concentrations of additives in the composite electrolyte are configured as follows: brightener 25~30 mg / L, leveling agent 35~40 mg / L, inhibitor 6~8 mg / L; the concentration of stress reliever is set according to its specific type: when N-(3-sulfopropyl)-saccharin sodium is used, the concentration is 15~25 mg / L; when JC-U2 is used, the concentration is 0.5~1.5 mg / L; when JC-IBE is used, the concentration is 10~25 mg / L.
[0010] Furthermore, the concentrations of the electrolyte components in the composite electrolyte are configured as follows: based on copper ions, the copper ion concentration is 80~95 g / L (copper ions are provided by copper sulfate); the sulfuric acid concentration is 100~130 g / L.
[0011] The composite electrolyte for low-stress lithium-ion battery copper foil provided by this invention can be used in the preparation of low-stress lithium-ion battery copper foil.
[0012] This invention also provides a method for preparing low-stress lithium-ion battery copper foil, comprising the following steps: S1. The above-mentioned low-stress lithium-ion battery copper foil is added to an electrolytic cell with a composite electrolyte, and electrolytic copper foil is obtained by electrolytic deposition. S2. The electrolytic copper foil is immersed in a nitrogen-purified nonionic foaming agent aqueous solution for at least 30 min, dried, and then annealed under an inert atmosphere at a temperature of 200-300℃ for 1-2 h with an inert gas flow rate of 2-5 L / min. Finally, the copper foil is cooled to room temperature at a uniform rate under an inert atmosphere to obtain the low-stress lithium battery copper foil.
[0013] Further, in step S1, the steps for preparing electrolytic copper foil by electrolytic deposition are as follows: S11. Using a titanium plate as the cathode and anode, the above-mentioned low-stress lithium-ion battery copper foil is added to the electrolytic cell with a composite electrolyte. During electrolysis, the electrolysis temperature in the electrolyte is controlled at 50~60℃, the current density is controlled at 30~70 A / dm², and the electrolysis time is controlled at 1~5 min according to the target copper foil thickness, so that the copper foil thickness deposited on the cathode plate surface reaches 6 μm. S12. Peel the obtained copper foil off the cathode plate and clean it to remove residual electrolyte and impurities on the surface of the copper foil, so as to avoid local stress caused by residual impurities, and thus obtain electrolytic copper foil.
[0014] Preferably, in step S11, the preferred parameters in the composite electrolyte are: copper sulfate concentration of 85 g / L and sulfuric acid concentration of 110 g / L, and the preferred electrolysis process parameters are temperature of 55℃ and current density of 50 A / dm². Under this parameter range, the copper ion deposition rate is moderate, the grain growth is dense and uniform, and there is no stress accumulation.
[0015] Furthermore, in step S2, the concentration of the nonionic foaming agent in the aqueous solution is 0.1~0.5 g / L. The nonionic foaming agent can form a uniform foam layer on the copper foil surface, further isolating oxygen, while improving the wettability of the copper foil surface and enhancing the adhesion of subsequent coatings.
[0016] Furthermore, in step S2, the copper foil that has been soaked in a nitrogen-purified nonionic foaming agent aqueous solution is dried at a temperature of 60~80℃ for 2~4 hours. During the drying process, the relative humidity of the environment is strictly controlled at 30~50% to avoid deformation of the copper foil and generation of internal stress due to uneven drying rate or excessive humidity.
[0017] Furthermore, in step S2, after annealing, the copper foil is cooled to room temperature at a rate of 5°C / min under an inert atmosphere.
[0018] Unlike existing technologies, this invention has the following advantages: 1. This invention constructs a low-stress copper foil-specific composite electrolyte system consisting of a brightener, a leveling agent, an inhibitor, and a stress reliever. The brightener refines the copper foil grains, improves surface brightness, and inhibits abnormal grain growth, reducing grain boundary defects. The leveling agent adsorbs onto the cathode surface, ensuring uniform copper ion deposition, reducing surface roughness, and preventing stress concentration caused by localized deposition protrusions. The inhibitor suppresses excessive localized deposition on the copper foil surface, regulates the copper ion deposition rate, and ensures dense grain growth. The stress reliever, as the core additive, adjusts the copper ion deposition pattern by adsorbing onto the cathode surface, reducing grain boundary defects and lattice distortion, thereby disrupting stress accumulation. This invention reduces internal stress in the copper foil from the source of copper ion deposition by precisely controlling the type and amount of each additive.
[0019] 2. Unlike traditional composite electrolytes, the low-stress lithium-ion battery copper foil composite electrolyte of this invention eliminates the introduction of chloride ions and collagen / gelatin components, thus fundamentally avoiding chloride-induced (111) crystal plane preferred orientation growth and dendrite and burr defects, as well as the inherent defects of collagen / gelatin components such as aggravated anodic oxidation corrosion, increased copper foil brittleness, and easy spoilage during storage. At the same time, through the synergistic effect of multiple components, this invention enables the copper foil to obtain a uniform and fine equiaxed crystal structure during the deposition stage, eliminating the anisotropy and uneven stress distribution caused by coarse columnar crystals in traditional processes. While effectively reducing internal stress, it also takes into account the synergistic improvement of tensile strength and elongation, which can meet the industrial continuous mass production requirements of 6μm ultrathin lithium-ion battery copper foil.
[0020] 3. Based on the above-mentioned composite electrolyte, the low-stress lithium-ion battery copper foil preparation method provided by the present invention further optimizes parameters such as current density and electrolyte temperature to achieve high-precision control of the electrodeposition process, so as to ensure uniform deposition of copper ions and dense grain growth during electrolysis, and achieve synergistic mechanical properties of low stress, high tensile strength and high elongation of copper foil.
[0021] 4. This invention also incorporates a controllable post-processing technology integrating humidity-controlled drying, inert atmosphere annealing, and uniform cooling: By precisely controlling the drying rate, deformation and new internal stress in the copper foil caused by uneven drying rates and excessively high ambient humidity are avoided; the annealing process eliminates residual stress from the copper foil electrodeposition process, while further refining the grains and improving the overall mechanical properties of the copper foil; uniform cooling avoids excessive temperature differences between the inside and outside of the copper foil caused by excessively rapid cooling, preventing the generation of thermal stress. The synergistic effect of these processes effectively suppresses the generation of secondary stress, isolates copper foil oxidation, and achieves precise control over the warpage of the copper foil. Detailed Implementation
[0022] The present invention will be further described below with reference to preferred embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention.
[0023] Unless otherwise specified, all materials and reagents used in the following examples are commercially available; and all methods used in the following examples are conventional methods.
[0024] This invention provides an electrolyte for low-stress lithium-ion battery copper foil, comprising an electrolyte and additives. The electrolyte comprises copper sulfate and sulfuric acid, and the additives comprise: a brightener, a leveling agent, an inhibitor, and a stress reliever. In the following examples, the brightener used is SH110 (sodium thiazolinyl dithiopropane sulfonate), purchased from Wuhan Jihechang New Material Co., Ltd. Its function is to refine the copper foil grains, improve surface brightness, inhibit abnormal grain growth, and reduce grain boundary defects. The addition amount is 25-30 mg / L, preferably 25 mg / L. The leveling agent used is HEC (hydroxyethyl cellulose), purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Its function is to adsorb onto the cathode surface, ensuring uniform copper ion deposition, reducing surface roughness, and avoiding stress concentration caused by localized deposition protrusions. The addition amount is 35-40 mg / L, preferably 40 mg / L. The inhibitor used is PEG (polyethylene glycol), its function is to inhibit excessive localized deposition on the copper foil surface, regulate the copper ion deposition rate, and ensure dense grain growth. The addition amount is 6-8 mg / L, preferably 6 mg / L. mg / L; The stress reliever is selected from one of SAPS (N-(3-sulfopropyl)-saccharin sodium salt), JC-U2 or JC-IBE, all purchased from Wuhan Jihechang New Material Co., Ltd., as the core additive. Its function is to adjust the copper ion deposition mode by adsorbing on the cathode surface, reduce grain boundary defects and lattice distortion, thereby destroying stress accumulation. The addition amount of SAPS is 15~25 mg / L, the addition amount of JC-U2 is 0.5~1.5 mg / L, and the addition amount of JC-IBE is 10~25 mg / L.
[0025] The nonionic foaming agent used in the following examples is an aqueous solution system, with the following concentrations: fatty alcohol polyoxyethylene ether (AEO-9) 0.1-0.3 g / L, alkyl glycoside (APG0810) 0.1-0.2 g / L, and deionized water as the solvent.
[0026] The following specific embodiments further illustrate the composite electrolyte for low-stress lithium-ion battery copper foil and the preparation method of low-stress lithium-ion battery copper foil of the present invention.
[0027] Example 1 This embodiment provides a composite electrolyte for low-stress lithium-ion battery copper foil, comprising an electrolyte and additives. The electrolyte includes copper sulfate and sulfuric acid, and the additives include a brightener, a leveling agent, an inhibitor, and a stress reliever. The brightener is selected from SH110, the leveling agent from HEC, the inhibitor from PEG, and the stress reliever from SAPS.
[0028] The preparation process of the composite electrolyte for the low-stress lithium-ion battery copper foil is as follows: S1. Dissolve SH110, HEC, PEG, and SAPS in a base electrolyte to prepare single-component stock solutions with a concentration of 1 g / L; the base electrolyte is an aqueous solution containing copper sulfate and sulfuric acid (preferably, copper ion concentration of 85 g / L and sulfuric acid concentration of 110 g / L). S2. Measure 25 mL of SH110 stock solution, 40 mL of HEC stock solution, 6 mL of PEG stock solution, and 15 mL of SAPS stock solution respectively, and mix them. S3. Add basic electrolyte to the mixture obtained in step S2 until the total volume is 1L, stir evenly, and the low-stress lithium battery copper foil composite electrolyte is obtained; the concentration of SH110 in the electrolyte is 25mg / L, the concentration of HEC is 40mg / L, the concentration of PEG is 6mg / L, and the concentration of SAPS is 15mg / L.
[0029] Examples 2-9 Examples 2-9 also provide composite electrolytes for low-stress lithium-ion battery copper foil, differing from Example 1 in the type and amount of stress reliever, as shown in Table 1. The types, amounts, and preparation methods of the remaining additives are the same as in Example 1, and will not be repeated here.
[0030] Table 1. Types and dosages of stress relievers in each embodiment
[0031] Comparative Example 1 Comparative Example 1 provides a composite electrolyte for lithium-ion battery copper foil, which differs from Example 1 in that it does not contain a stress reliever, while the remaining components and amounts are the same as in Example 1.
[0032] The preparation process of this lithium battery copper foil composite additive is as follows: S1. Dissolve SH110, HEC, and PEG in a base electrolyte to prepare single-component stock solutions with a concentration of 1 g / L; the base electrolyte is an aqueous solution containing copper sulfate and sulfuric acid (preferably, the copper ion concentration is 85 g / L and the sulfuric acid concentration is 110 g / L). S2. Measure 25 mL of SH110 stock solution, 40 mL of HEC stock solution, and 6 mL of PEG stock solution respectively, and mix them. S3. Add basic electrolyte to the mixture obtained in step S2 until the total volume is 1L, stir evenly, and the composite electrolyte for lithium battery copper foil is obtained; the concentration of SH110 in the electrolyte is 25mg / L, the concentration of HEC is 40mg / L, and the concentration of PEG is 6mg / L.
[0033] Application Example 1 The low-stress lithium-ion battery copper foil additive prepared in Example 1 of this application case is used in the preparation method of low-stress lithium-ion battery copper foil. The specific preparation process is as follows: S1. Preparation of electrolytic copper foil: The low-stress lithium-ion battery copper foil composite electrolyte prepared in Example 1 was used as the working electrolyte and added to the electrolytic cell. A titanium plate was used as both the cathode and anode. The electrolyte temperature was controlled at 55°C, the current density at 50A / dm², and the electrolysis time (generally within 1~5 min). Electrolysis was stopped when the thickness of the copper foil deposited on the cathode plate reached 6 μm. The generated copper foil was then peeled off from the cathode plate and washed three times with deionized water to obtain the electrolytic copper foil. S2. Post-treatment of electrolytic copper foil: S21. The electrolytic copper foil is immersed in a nitrogen-purified nonionic foaming agent aqueous solution for at least 30 min, wherein the concentration of the nonionic foaming agent in the aqueous solution is 0.3 g / L, which is used to improve the surface wettability of the copper foil. S22. Dry the soaked copper foil at 60~80℃ for 2~4 hours, controlling the relative humidity at 30~50%; S23. After drying, annealing is performed under an inert atmosphere at a temperature of 250℃ and a holding time of 1.5 h, with an inert gas flow rate of 3 L / min. S24. After annealing, the copper foil is cooled to room temperature at a uniform rate of 5°C / min under an inert atmosphere to obtain the low-stress lithium battery copper foil.
[0034] Application Examples 2-9 and Comparative Application Example 1 Application Examples 2-9 were prepared using the low-stress lithium-ion battery copper foil composite additives obtained in Examples 2-9, and the preparation process and process parameters were consistent with those in Application Example 1. In Comparative Application Example 1, the lithium-ion battery copper foil additives of Comparative Example 1 were used to prepare copper foil, and the preparation process and process conditions were the same as those in Application Example 1.
[0035] Performance testing The present invention conducts performance tests on the lithium battery copper foils prepared in the above application examples and comparative application examples. The test methods for each index are performed in accordance with the relevant provisions of SJ / T 11483-2025 "Electrolytic Copper Foil for Lithium-ion Batteries". The results are shown in Table 2.
[0036] Among them, tensile strength and elongation were tested according to the methods specified in Chapter 7.1 of GB / T 29847-2025; Warpage shall be tested according to the method specified in Appendix C of GB / T 5230-2020.
[0037] Table 2 Performance Test Results
[0038] The above results indicate that the lithium-ion battery copper foil of the present invention has good tensile strength, elongation and low warpage, and can effectively meet the requirements of high energy density, high rate and long cycle lithium-ion batteries.
[0039] In summary, the low-stress lithium-ion battery copper foil preparation method disclosed in this invention constructs a dedicated synergistic composite electrolyte system of brightener, leveling agent, inhibitor, and stress reliever, combined with a precisely controlled electrolysis process and a controllable post-treatment process of controlled-humidity drying, inert annealing, and uniform-speed cooling. This forms an integrated low-stress lithium-ion battery copper foil preparation technology solution. It achieves precise control of the internal stress of the copper foil from the copper ion deposition source, deposition process, and post-treatment process. At the same time, it takes into account the synergistic optimization of the tensile strength, elongation, warpage, and surface properties of the copper foil, effectively solving industry pain points such as production strip breakage, low downstream processing yield, battery cycle life degradation, and safety hazards caused by excessive stress in traditional lithium-ion battery copper foil.
[0040] The process parameters of this invention have all been industrially verified, with strong operational controllability and good repeatability. It can realize the large-scale industrial preparation of 6 μm ultrathin lithium battery copper foil. The low-stress lithium battery copper foil produced exhibits excellent performance in mechanical properties, dimensional stability and processing adaptability. It can meet the high-end application requirements of various lithium-ion batteries such as power batteries, energy storage batteries and consumer electronics batteries for negative electrode current collectors, and adapt to the development trend of high energy density, thinness and long cycle life of lithium batteries.
[0041] This invention possesses unique technical advantages in additive system design, process parameter coordination, and post-processing optimization. It not only improves the yield and production efficiency of lithium-ion battery copper foil manufacturers and reduces production costs, but also provides core material support for performance upgrades and quality improvements in the downstream lithium-ion battery industry, driving technological progress across the lithium-ion battery supply chain. Furthermore, the technical approach of this invention can be further extended to the preparation of thinner lithium-ion battery copper foil, demonstrating excellent technological extensibility and market application prospects. It has significant promotional value in the field of new energy battery materials and can generate substantial economic and social benefits.
Claims
1. A composite electrolyte for low-stress lithium-ion battery copper foil, characterized in that, It includes electrolytes and additives, wherein the electrolytes include copper sulfate and sulfuric acid, and the additives include: brighteners, leveling agents, inhibitors, and stress relievers; The brightener is sodium thiazolinyl dithiopropane sulfonate; the leveling agent is hydroxyethyl cellulose; the inhibitor is polyethylene glycol; and the stress reliever is selected from one of N-(3-sulfopropyl)-saccharin sodium, JC-U2, or JC-IBE.
2. The composite electrolyte for low-stress lithium-ion battery copper foil according to claim 1, characterized in that, The concentrations of additives in the composite electrolyte are as follows: brightener 25~30 mg / L, leveling agent 35~40 mg / L, inhibitor 6~8 mg / L; the concentration of stress reliever is set according to the specific type selected: when N-(3-sulfopropyl)-saccharin sodium is selected, the concentration is 15~25 mg / L; when JC-U2 is selected, the concentration is 0.5~1.5 mg / L; when JC-IBE is selected, the concentration is 10~25 mg / L.
3. The composite electrolyte for low-stress lithium-ion battery copper foil according to claim 2, characterized in that, The electrolyte concentrations in the composite electrolyte are configured as follows: based on copper ions, the copper ion concentration is 80~95 g / L, provided by copper sulfate; the sulfuric acid concentration is 100~130 g / L.
4. Application of composite electrolyte for low-stress lithium-ion battery copper foil in the preparation of low-stress lithium-ion battery copper foil.
5. A method for preparing low-stress lithium-ion battery copper foil, characterized in that, Includes the following steps: S1. The low-stress lithium-ion battery copper foil as described in any one of claims 1 to 3 is added to an electrolytic cell, and electrolytic copper foil is obtained by electrolytic deposition. S2. Immerse the electrolytic copper foil in a nitrogen-purged nonionic foaming agent aqueous solution for at least 30 min, dry it, and then anneal it under an inert atmosphere at a temperature of 200-300°C for 1-2 h with an inert gas flow rate of 2-5 L / min. Finally, cool the copper foil to room temperature at a uniform rate under an inert atmosphere to obtain the low-stress lithium-ion battery copper foil.
6. The method for preparing low-stress lithium-ion battery copper foil according to claim 5, characterized in that, In step S1, the steps for preparing electrolytic copper foil by electrolytic deposition are as follows: S11. Using a titanium plate as the cathode and anode, the low-stress lithium-ion battery copper foil is added to the electrolytic cell with a composite electrolyte. During electrolysis, the electrolysis temperature is controlled at 50~60℃, the current density is controlled at 30~70 A / dm², and the electrolysis time is controlled at 1~5 min according to the target copper foil thickness. Electrolysis is stopped when the copper foil thickness deposited on the cathode plate reaches 6 μm. S12. Peel the copper foil produced in step S11 off the cathode plate and clean it to remove residual electrolyte and impurities on the surface of the copper foil, thereby obtaining electrolytic copper foil.
7. The method for preparing low-stress lithium-ion battery copper foil according to claim 5, characterized in that, In step S2, the concentration of the nonionic foaming agent in the aqueous solution is 0.1~0.5 g / L.
8. The method for preparing low-stress lithium-ion battery copper foil according to claim 5, characterized in that, In step S2, the copper foil that has been soaked in a nitrogen-purified nonionic foaming agent aqueous solution is dried at a temperature of 60~80℃ for 2~4 hours, and the relative humidity of the environment is strictly controlled at 30~50% during the drying process.
9. The method for preparing low-stress lithium-ion battery copper foil according to claim 5, characterized in that, In step S2, after annealing, the copper foil is cooled to room temperature at a rate of 5°C / min under an inert atmosphere.
Citation Information
Patent Citations
Production process of low-warpage electrolytic copper foil
CN102965698A
Production process of electrolytic copper foil with low warping degree
CN104762642A
Additive agent for 6-micrometer double-polished low-warpage electrolytic copper foil and production technology of electrolytic copper foil
CN109763152A
Additive and electroplating solution for preparing low-warpage high-tensile copper foil, low-warpage high-tensile copper foil and preparation method of low-warpage high-tensile copper foil
CN118292060A
Copper foil warping reducing agent and preparation method thereof
CN118957686A